Words and the Word language, poetics, and biblical interpretation - Prickett, Stephen 1939-2020 (Cambridge University Press, 1986)
First published in 1986, Stephen Prickett's Words and the 'Word' has had a major impact among scholars of literature and literary theory as well as among theologians and biblical critics. In this highly-acclaimed book Prickett pursues the question of the relationship between religion and poetics, and in particular the nature of religious language, investigating the hermeneutic, epistemological and linguistic reverberations of eighteenth, nineteenth, and twentieth-century theories of biblical interpretation